Intraoperative 3D imaging in the treatment of elbow fractures: a retrospective analysis of indications, intraoperative revision rates, and implications in 36 cases - Schnetzke, Marc; Fuchs, Julia; Vetter, Sven Y.; Beisemann, Nils; Keil, Holger; Grützner, Paul Alfred; Franke, Jochen (BMC medical imaging, 2016)
Three-dimensional (3D) imaging with a mobile C-arm has proven to be a valuable intraoperative tool in trauma surgery. However, little data is available concerning its use in the treatment of elbow fractures. The aim of the current study was to determine the intraoperative findings and consequences of 3D imaging in the treatment of elbow fractures.
Gesehen am 19.02.2020